Non-symmetrized Hyperspherical Harmonics Method for Non-equal Mass Three-Body Systems - Nannini, Alessia; Marcucci, Laura E. (Frontiers in Physics, 2018)
The non-symmetrized hyperspherical harmonics method for a three-body system, composed by two particles having equal masses, but different from the mass of the third particle, is reviewed and applied to the 3H, 3He nuclei, and HΛ3 hyper-nucleus, seen respectively as nnp, ppn, and NNΛ three-body systems. The convergence of the method is first tested in order to estimate its accuracy. Then, the difference of binding energy between 3H and 3He due to the difference of the proton and the neutron masses is studied using several central spin-independent and spin-dependent potentials. Finally, the HΛ3 hypernucleus binding energy is calculated using different NN and ΛN potential models. The results have been compared with those present in the literature, finding a very nice agreement.